If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + 6(x + 5) = 4x + -1(3x + 9) Reorder the terms: 8 + 6(5 + x) = 4x + -1(3x + 9) 8 + (5 * 6 + x * 6) = 4x + -1(3x + 9) 8 + (30 + 6x) = 4x + -1(3x + 9) Combine like terms: 8 + 30 = 38 38 + 6x = 4x + -1(3x + 9) Reorder the terms: 38 + 6x = 4x + -1(9 + 3x) 38 + 6x = 4x + (9 * -1 + 3x * -1) 38 + 6x = 4x + (-9 + -3x) Reorder the terms: 38 + 6x = -9 + 4x + -3x Combine like terms: 4x + -3x = 1x 38 + 6x = -9 + 1x Solving 38 + 6x = -9 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 38 + 6x + -1x = -9 + 1x + -1x Combine like terms: 6x + -1x = 5x 38 + 5x = -9 + 1x + -1x Combine like terms: 1x + -1x = 0 38 + 5x = -9 + 0 38 + 5x = -9 Add '-38' to each side of the equation. 38 + -38 + 5x = -9 + -38 Combine like terms: 38 + -38 = 0 0 + 5x = -9 + -38 5x = -9 + -38 Combine like terms: -9 + -38 = -47 5x = -47 Divide each side by '5'. x = -9.4 Simplifying x = -9.4
| 9y(5)-2(2+7-18)= | | x=x^2-10x-11 | | 5y=12x-8 | | 20x+14y=3748 | | X(1-x)=0.02 | | 3x-9=3x+9 | | .5a^2+a-12=0 | | -4x-7(1-x)=-11x+9(3x+5) | | (x-3.5)^2/3=150 | | 32=5+-3t | | -1/2x+3=x-7 | | x=x+(.005n*x) | | (4x^2-3x^3)-(9x^2-5x^3)=-5x^2+2x^3 | | -4x-7(1-x)=11x+9(3x+5) | | -6x^2+64x+192=0 | | 4x^2+8x-26=(x+3)(x-2) | | 20x+10=80x+50 | | y=x+(.06*x) | | 6x+3=4x-13 | | z^2+6z-9=6z | | 3(x+6)=7x-14 | | -3x^2+32x+96=0 | | 2(0)-5x=10 | | (4x^2-3x^3)-(9x^2-5x^3)=-3x^5 | | y=x+(.005n*x) | | 4x-8=33 | | X(4x)=64 | | 1/3y=x | | 11+12k=-25 | | 3x+4+5x=20 | | z/10=13 | | 3(0)-2x=6 |